Report on hydrozoans (Cnidaria), excluding Stylasteridae, from the Emperor Seamounts, western North Pacific Ocean - Calder, Dale R.; Watling, Les (Zootaxa, 2021)
Fourteen species of hydroids, collected during August 2019 by ROV SuBastian of the Schmidt Ocean Institute, are reported from the Emperor Seamount chain in the western North Pacific Ocean. Two others, Candelabrum sp. and Eudendrium sp., were observed only on videos taken by the ROV. From collections and video observations, eight species of hydroids were found at Jingū Seamount, three at Yomei, Nintoku, and Annei seamounts, and one at Koko Seamount and Hess Rise. At Suiko and Godaigo seamounts, hydroids were seen in videos but they could not be identified. Latebrahydra schulzei, an endobiotic associate of the hexactinellid sponge Walteria flemmingii Schulze, 1886 from Annei Seamount and Hess Rise, is described as a new genus and species tentatively attributed to Hydractiniidae L. Agassiz, 1862. Another new species, Hydractinia galeai, is described from Jingū Seamount. Among its distinctive characters is a zooid termed a sellectozooid, likely serving in both food capture and defence. Hydroids examined from Yomei, Nintoku, and Jingū seamounts are elements of a cold-water fauna occurring in the North Pacific Boreal Bathyal province, while those of Annei and Koko seamounts, and Hess Rise, are part of the biota of the Central North Pacific Bathyal province. Hydroids identified as Bouillonia sp., from Nintoku Seamount, represent the first record of this predominantly deep water tubulariid genus in the North Pacific Ocean. Bonneviella superba Nutting, 1915, from Jingū Seamount, is reported for the first time outside the Aleutian Islands. Bonneviella cf. gracilis Fraser, 1939, known elsewhere only from Dease Strait in the western Canadian Arctic, was also collected on Jingū. In addition to hydroids, medusae of Ptychogastria polaris Allman, 1878 were observed on videos from Nintoku, Jingū, Annei, and Koko seamounts at depths between 2423–1422 m. An unidentified siphonophore was observed near bottom at 2282 m on Nintoku Seamount.